PENERAPAN PELAPORAN KEUANGAN BEDASARKAN ISAK 35 PADA MASJID SUNAN AMPEL GUMUKMAS - Fizaini, Muhammad; Yuliarti, Norita Citra; Ari Sita Nastiti, Ari Sita Nastiti Ari Sita Nastiti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
This study aims to determine the existing forms of financial reporting and also to determine the application of financial reporting at the Sunan Ampel Mosque, Kec. Gumukmas Kab. Jember based on ISAK No. 35. The method used is descriptive qualitative. Sources of data using primary and secondary data collected by researchers using interviews, observation, and documentation techniques. In this study, researchers conducted data analysis by collecting data, explaining financial management procedures, reconstructing, presenting to be able to draw a conclusion. The results of the study show that the financial records of the Sunan Ampel Mosque still use a simple method. Financial recording is only done if there is cash in and cash out (cash basis). Then the amount of cash in, cash out, and total cash is reported every Friday by conveying it using the mosque's microphone. Then the preparation of the financial reports of the Sunan Ampel Mosque which was prepared based on ISAK No. 35 produce financial reports that are more structured and more detailed, not only related to cash in and cash out.